P111 Exhaled breath biomarkers in pulmonary aspergillosis. (15th November 2017) - Talbot, ST; White, I; Hobson, A; Wilkinson, M; Simpson, A; Novak-Frazer, L; Gioan-Tavernier, G; Denning, DW; Fowler, SJ
Abstract : Introduction: Pulmonary aspergillosis has a substantial global health burden, and is difficult to diagnose and treat. Aspergillus metabolism Results in measurable changes in volatile organic compounds (VOCs) and these may be detectable in the breath. In this pilot study, we sought to measure the abundance of VOCs in the breath samples of patients with pulmonary aspergillosis, and identify any difference in VOC profile between patients with and without Aspergillus in their airway. Methods: Patients were recruited while attending the National Aspergillosis Centre and University Hospital South Manchester, and categorised as Aspergillus positive or Aspergillus negative on the basis of high volume sputum culture. Lower airway breath samples were collected from patients and analysed by thermal desorption gas chromatography mass spectrometry (TD-GC-MS). A target library based upon previous literature reports of Aspergillus- related VOCs was used to deconvolve the raw GC-MS data. Peak area on the chromatogram for each sample was calculated as a measure of VOC abundance. Potentially discriminating compounds between the groups were identified by univariate analysis. Results: 18 patients were recruited, and were allocated to the following groups: culture-positive (n=7), and culture-negative (n=11). Analysis of patient demographics and potential breath contaminants revealed no significant difference between groups. The targeted analysis incorporated 35 VOCs. Of these, 2 were found to be significantly more abundant (figure 1 ) in culture-positive than culture-negative patient samples. These compounds most likely represent limonene (p=0.017) and alpha-terpinene (p=0.007). Conclusion: This pilot study has identified differences in the exhaled VOC profile of patients with sputum culture-positive and culture-negative pulmonary aspergillosis. The finding of elevated levels of terpenoids in the breath of culture positive patients concurs with current understanding of the Aspergillus volatome in vivo and in vitro . A larger study using multivariate analysis should be performed to identify discriminating exhaled VOC signatures in patients with aspergillosis for future clinical use.